Synthesis, characterization and metal ion detection of novel fluoroionophores based on heterocyclic substituted alanines - Costa, Susana P. G. (2007)
The synthesis of new fluorescent probes containing the thiophene and benzoxazole moieties combined with an alanine residue is described. The resulting highly fluorescent heterocyclic alanine derivatives respond via a quenching effect, with paramagnetic Cu(II) and Ni(II) metal ions and with diamagnetic Hg(II), as shown by the absorption and steady-state fluorescence spectroscopy studies. The formation of mononuclear or dinuclear metal complexes was postulated based on the presence of the free carboxylic acid as binding site and also with the interaction with the donor atoms in the chromophore. Interaction with other important biological metal ions such as Zn(II), Ca(II) and Na(I) was also explored.